(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
This work analyses the regulation of abortion in the San Marino legal system after the 2022 referendum. The first paragraph focuses on the right to abortion and how it is connected to the woman’s right to self-determination versus the right to life recognised by the foetus; for this reason, a balance between these two opposing rights is required. Secondly, this paper analyses both the ruling on the referendum request by the San Marino Constitutional Court and the legislation after the referendum.